2014
DOI: 10.1088/1748-9326/9/10/104006
|View full text |Cite
|
Sign up to set email alerts
|

Robust features of future climate change impacts on sorghum yields in West Africa

Abstract: West Africa is highly vulnerable to climate hazards and better quantification and understanding of the impact of climate change on crop yields are urgently needed. Here we provide an assessment of near-term climate change impacts on sorghum yields in West Africa and account for uncertainties both in future climate scenarios and in crop models. Towards this goal, we use simulations of nine bias-corrected CMIP5 climate models and two crop models (SARRA-H and APSIM) to evaluate the robustness of projected crop yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
98
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 51 publications
15
98
0
2
Order By: Relevance
“…This is consistent to results by Rosenzweig et al (2014) who reported model agreement on direction of yield change but varying in magnitude. Sultan et al (2014) observed high consistence across climate and crop models in climate and impacts projections on sorghum between the western and eastern parts of the Sahel. In East Africa, a study by Thornton et al (2009) similarly showed yield decreases for maize over the region ranging between 1% and 15% across emissions scenarios and climate models, largely as a result of temperature increase.…”
Section: Model Evaluation and Crop Yield Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent to results by Rosenzweig et al (2014) who reported model agreement on direction of yield change but varying in magnitude. Sultan et al (2014) observed high consistence across climate and crop models in climate and impacts projections on sorghum between the western and eastern parts of the Sahel. In East Africa, a study by Thornton et al (2009) similarly showed yield decreases for maize over the region ranging between 1% and 15% across emissions scenarios and climate models, largely as a result of temperature increase.…”
Section: Model Evaluation and Crop Yield Projectionsmentioning
confidence: 99%
“…The influence of the improved agro-systems on crop sensitivity to climate change is still a matter of debate (Turner & Rao, 2013;Sultan et al, 2014). While on the one hand, Turner and Rao (2013) show minimum stress from warming temperatures under the current low-input production systems (no-N fertilizer added) compared to improved systems (with adequate N fertilization), Sultan et al (2014) show that increasing fertilizer inputs in the Sahel agricultural system could make it more responsive to climatic stresses and produce more negative impacts (in a relative sense, %) in crop yields under climate change. Results from both studies suggest that sorghum yields under current smallholders' low-input systems would be resilient or even increase under increasing temperatures.…”
Section: Effect Of Adaptation Optionsmentioning
confidence: 99%
“…For the future, the IPCC 2013 [120] and IPCC 2017 [121] climate projections suggest an increase in rainfall in West Africa due to global warming, which would favor the dynamics of the monsoon, except in the western part of West Africa, where they suggest a dry period near the Atlantic Ocean in the near future (Biasutti [122] and Sultan [123]). However, the models are not accurate in their depiction of regional West African climates [124].…”
mentioning
confidence: 99%
“…agriculture | climate change | crop | sorghum | warming S orghum (Sorghum bicolor) is predominantly grown in the arid and semiarid regions of the world, where heat stress is known to induce significant yield losses (1)(2)(3)(4). Globally, sorghum is positioned as the fifth most economically important cereal and plays a critical role in providing food, fodder, and fuel (5,6).…”
mentioning
confidence: 99%